Getting Data from Telegram using API Calls - Christodoulou, Andreas (My University, 2023)
With the continuous development of Technology and the ever-greater use of social media, the risks naturally increased and continue to increase. Naturally, Telegram was also affected by this situation. In my thesis, libraries and API calls will be used, which will return some data. These data will be stored in a database where they will be subject to processing. Also, this thesis has implemented a frond-end to display the data, and the user can run a method. From the front end, the user will also have the ability to delete all data from the base. In addition, to make it possible for the code to run in a dynamic way, it had to be implemented to be able to read the link for each separate channel and create a different JSON file for each one. Furthermore, while the code is running, there is a method called to collect and store in a text record all the links found in the JSON file regardless of the platform they belong to. In this way, we can manage a large volume of data and collect information to make our goal easier. In order to make the implementation of all this possible, we had to face various problems, which will be analyzed in detail below. Furthermore, an extensive analysis of the materials used will be given. Finally, future considerations for this thesis will be mentioned.
Keywords: social media; Telegram; API